Neonatal mortality: a scenario in a tertiary level hospital of a developing country - Mamunur A.K.M. Rashid; Habibur C.H. Rasul; Mahbub S. Hafiz (MDPI AG, 2010)
This study was designed to observe the overall neonatal mortality and pattern of neonatal death in a developing country. The factors related to neonatal mortality are also analyzed. This retrospective study was carried out in all pediatric patients in a tertiary level hospital of a developing country in the year 2008. Total neonatal (0-28 days) and non-neonatal (after 28 days-12 years) admissions and death records were analyzed. There were a total of 3,194 admissions in the year 2008. Neonatal and non-neonatal admissions numbered 942 and 2,252, respectively. There were a total of 146 (15.5%) neonatal deaths among neonatal admissions and 114 (5.06%) non-neonatal deaths among non-neonatal admissions. There were 87 (59.59%) preterm related deaths and 98 (67.12%) deaths due to Low Birth Weight (LBW). There were 102 (70%) deaths among neonates who had no antenatal follow-up. Mother's age was under 20 years in 80 (55%) cases of neonatal death. The number of neonatal deaths is high in developing countries. Preterm with Low Birth Weight (LBW) is the major cause of mortality. Regular antenatal care and social discouragement of early marriage can greatly reduce neonatal death. Skilled and trained nursing care is necessary for the survival of the preterm and Low Birth Weight (LBW) baby in the hospitals of developing countries.